Fixed versus flexible exchange rates: Evidence from developing countries - Mathias Hoffmann (University of Cologne, Centre for Financial Research (CFR), 2005)
This paper investigates the formalisation that in a small open economy flexible exchange rates act as a 'shock absorber' and mitigate the effects of external shocks more effectively. An intertemporal small open economy model with nominal rigidities, in which real shocks generate internal imbalances under fixed and flexible exchange rates, is laid out. The role of world interest rate and world output shocks in driving output, trade imbalances and real exchange rate fluctuations is investigated. Using a sample of 38 developing countries, the paper assesses whether the responses of real GDP, the trade balance and the real exchange rate to world real interest rate and world output shocks differ across exchange rate regimes.
Keywords: C33; F31; F41; 330; Small Open Economies; Exchange Rate Regimes; Panel VAR